Peningkatan Kualitas Sdm Pariwisata Melalui Pendidikan Terintegrasi: Kolaborasi Perguruan Tinggi Vokasi Dengan Industri Pariwisata - Deden Saepudin; Didin Nurdin; Ilham Fajri; Dadi Indra Permana (Barista : Jurnal Kajian Bahasa dan Pariwisata, 2022)
The quality of tourism human resources is closely related to the quality of tourism education institutions. A good tourism educational institution will also produce good graduates, as candidates for quality tourism human resources. Thus efforts to improve tourism human resources begin with efforts to improve the quality of tourism education. This study analyzes how education is managed in tourism vocational higher education institutions, especialy at the NHI Bandung Tourism Academy and at Nusantara Jaya Depok Tourism Academy. The research method uses a qualitative approach with observation techniques, documentation studies and in-depth interviews with stakeholders. It consists of directors, heads of study programs, lecturers, practice instructors, heads of internal quality assurance, and students at the two institutions that are the locus of research. The results of the study show that to produce graduates who are ready to work and have experience working in the industry, tourism higher institutions must collaborate with the hospitality industry in implementing integrated practical learning (work based learning). This form of collaboration is realized by involving industrial practitioners in a number of activities, including: 1) Curriculum development and alignment; 2) Formation of a Steering Committee; 3) Teaching practitioner program; 4) Implementaion on the job training; 5) Sending students to part-time work program (casual); and 6) Guest lecture from industry practitioners. The implications of this collaboration will improve the quality of graduates which will ultimately contribute to improving the quality of tourism human resources.